Henkel highlights aerospace and automotive solutions at JEC 2016. Issue 5 (September 2016) - Miah, Razina; Leach, David; Kerstan, Frank; Marsalko, Timea
Abstract : Reinforced Plastics spoke with David Leach, Timea Marsalko and Frank Kerstan from Henkel about aerospace solutions, including lightweight surfacing films for composite materials and new composite innovations that have been developed for the automotive industry.